Gender Inequality in Khulʿ and Judicial Divorce: Feminist Islamic Family Law in Indonesia - Mayang Nurfatia; Mustiqowati Ummul Fithriyyah (MUWAZAH : jurnal kajian gender, 2026)
This article examines gender inequality in women-initiated divorce under Indonesian Islamic family law, focusing on khulʿ and judicial divorce (cerai gugat). The study aims to clarify how legal doctrine, court procedure, compensation rules, evidentiary burdens, social stigma, and post-divorce enforcement shape women’s access to marital dissolution within contemporary Indonesian courts and communities. Previous studies have discussed divorce procedures, patriarchal norms, and women’s vulnerability after divorce, but few have integrated classical fiqh, Indonesian legal doctrine, Islamic feminist theory, and local dispute-resolution practices into one coherent analytical framework. Using normative-philosophical library research and feminist legal analysis, the study analyzes Qur’anic divorce principles, classical fiqh texts, Indonesian family-law instruments, and contemporary scholarly literature. The findings show that inequality appears through five interrelated indicators: access to legal mechanisms, autonomy in decision-making, proportionality of procedural and financial burdens, protection from harm, and enforceability of post-divorce rights. The article argues that a gender-just reading should distinguish divine ethical principles from historically situated fiqh formulations, interpret khulʿ compensation through maʿrūf and iḥsān, and strengthen women’s legal agency through gender-sensitive adjudication, legal literacy, and community support. Its contribution is a feminist-Islamic evaluative model for legal interpretation, judicial practice, policy intervention, and future empirical research in Indonesian Islamic family law.